Peran Guru Dalam Menghadapi Anak Tantrum di Sekolah PAUD Al-Mukhlisin Bandar Sawah - Ansari, Yanti; Utami, Indi Dwi; Batubara, Yusnani; Suwandi (At-Tadris: Journal of Islamic Education, 2023)
Talking about child tantrums, of course the teacher also plays a big role in this. This is because development is a continuous process of change leading to maturity. Therefore, communication is very necessary in dealing with children with tantrums at school. Early childhood behavior is strongly influenced by the environment. So if children want to behave well, the environment must also be good. For parents and teachers, provide good behavior for children such as giving affection, love and dealing with children calmly and patiently. In addition, children should also be invited to speak with a sincere heart and soft and smooth language so that children get used to and imitate good things too. Tentrum occurs when a child's emotional development is hampered so that the child becomes frustrated and then expresses it through uncontrolled emotions and anger.